Preoperative embolization in the treatment of patients with metastatic epidural spinal cord compression: A retrospective analysis - Zhang, Bin; Yu, Haikuan; Zhao, Xiongwei; Cao, Xuyong; Cao, Yuncen; Shi, Xiaolin; Wang, Zheng; Liu, Yaosheng (Frontiers in Oncology, 2022)
Purpose: The purpose of the study was to assess the effectiveness and safety of preoperative embolization in the treatment of patients with metastatic epidural spinal cord compression (MESCC). Methods: A retrospective analysis of 138 MESCC patients who underwent decompressive surgery and spine stabilization was performed in a large teaching hospital. Among all enrolled patients, 46 patients were treated with preoperative embolization (the embolization group), whereas 92 patients did not (the control group). Patient’s baseline clinical characteristics, surgery-related characteristics, and postoperative neurological status, complications, and survival prognoses were collected and analyzed. Subgroup analysis was performed according to the degree of tumor vascularity between patients with and without preoperative embolization. Results: Patients with severe hypervascularity experienced more mean blood loss in the control group than in the embolization group, and this difference was statistically significant (P=0.02). The number of transfused packed red cells (PRC) showed a similar trend (P=0.01). However, for patients with mild and moderate hypervascularity, both blood loss and the number of PRC transfusion were comparable across the two groups. Regarding decompressive techniques, the embolization group (64.29%, 9/14) had a higher proportion of circumferential decompression in comparison to the control group (30.00%, 9/30) among patients with severe hypervascularity (P=0.03), whereas the rates were similar among patients with mild (P=0.45) and moderate (P=0.54) hypervascularity. In addition, no subgroup analysis revealed any statistically significant differences in operation time, postoperative functional recovery, postoperative complications, or survival outcome. Multivariate analysis showed that higher tumor vascularity (OR[odds ratio]=3.69, 95% CI [confident interval]: 1.30-10.43, P=0.01) and smaller extent of embolization (OR=4.16, 95% CI: 1.10-15.74, P=0.04) were significantly associated with more blood loss. Conclusions: Preoperative embolization is an effective and safe method in treating MESCC patients with severe hypervascular tumors in terms of intra-operative blood loss and surgical removal of metastatic tumors. Preoperative tumor vascularity and extent of embolization are independent risk factors for blood loss during surgery. This study implies that MESCC patients with severe hypervascular tumors should be advised to undergo preoperative embolization.